Paradoxical Effects of Tumor Shrinkage on Long-Term Survival of Cancer Patients - Hanin, Leonid (Frontiers in Applied Mathematics and Statistics, 2020)
In this article, we challenge the existing paradigm that greater tumor shrinkage at the end of treatment leads to longer patient survival. In particular, we identify biological conditions under which the exact opposite is true. A central role in our argument about the paradoxical effect of tumor shrinkage is played by the emergence and self-selection of subpopulations of increasingly faster proliferating cancer cells. This evolutionary factor is often at work during post-treatment tumor regrowth and has a decidedly negative impact on patient survival. We analyze various patterns of post-treatment tumor dynamics and show that if the clones generated by cancer cells present at the end of treatment or the start of a treatment break evolve independently then greater tumor shrinkage leads to progressive enrichment of the re-growing tumor with faster proliferating cells. Importantly, greater tumor shrinkage favors independent clonal expansion. Our findings explain numerous clinical cases where initial tumor shrinkage to undetectable levels was promptly followed by an aggressive tumor recurrence. They also suggest that indiscriminate use of tumor shrinkage as surrogate endpoint in clinical trials should be discouraged.